Improving mathematical performance through the problem-based learning model - Irawan, Melati Putri; Anggraini, Rini Dian; Syofni (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study addresses the low mathematics achievement levels among students in class VIII.2 at SMP Negeri 35 Pekanbaru during the 2023/2024 academic year. The research aims to enhance the learning process and improve mathematics achievement by implementing the Problem-Based Learning (PBL) model. This study employs Classroom Action Research to identify problems and implement targeted actions to resolve them. The subjects comprised 19 male students and 20 female students with heterogeneous ability levels. The research instruments included the Flow of Learning Objectives, Teaching Modules with attached Student Worksheets, Diagnostic Assessments, Formative Assessments, and Summative Assessments. Observation sheets and learning outcome tests were used for data collection. The results indicate significant improvements in the learning process across cycles, as demonstrated by increased mathematics achievement. The number of students meeting the Learning Objective Achievement Criteria rose from 17 students (43.59%) in Cycle I to 25 students (64.10%) and further to 29 students (74.36%) in Cycle II. The study concludes that the application of the PBL model effectively improved both the learning process and mathematics achievement in class VIII.2 at SMP Negeri 35 Pekanbaru during the 2023/2024 academic year, particularly on the topic of the System of Linear Equations in Two Variables.